Composition as well as preparation method and application thereof

By controlling the opposite of the Zeta potential of the active substance and the cellulose, and using the flexibility and network structure of the cellulose for electrostatic adsorption and hydrogen bonding, the problem of the existing skin active ingredients in the non-specific pH range is solved, and the stable and sustained release effects of the active substance are achieved.

CN119524148AActive Publication Date: 2025-02-28INNOVATION CENT FOR CLEAN AIR SOLUTIONS +1
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202510106443.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-23
Publication Date
2025-02-28
Estimated Expiration
2045-01-23

AI Technical Summary

Technical Problem

Existing skin active ingredients are unstable outside a specific pH range, easily decompose or deteriorate, and temperature and light also affect their stability.

Method used

By controlling the Zeta potential of the active substance and the Zeta potential of the cellulose, the cellulose's flexibility and network structure are used for electrostatic adsorption and hydrogen bonding, and the active substance is physically embedded to form a stable composition to achieve a sustained release effect.

Benefits of technology

Effectively stabilize the spatial structure of the active substance, achieve the sustained release effect, and avoid the decomposition or deterioration of the active substance caused by changes in pH, temperature and light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524148A_ABST
    Figure CN119524148A_ABST
Patent Text Reader

Abstract

The invention provides a composition and a preparation method and application thereof, the composition comprises cellulose and an active substance, the Zeta potential or charge property of the active substance is opposite to the Zeta potential or charge property of the cellulose, the absolute value of the Zeta potential of the active substance is 10-100 mV, and the sum of the absolute value of the Zeta potential of the cellulose and the absolute value of the Zeta potential of the active substance is 25-200 mV. The cellulose can form relatively strong electrostatic adsorption and / or hydrogen bonding and physical embedding with the active substances, stabilizes the space structure of the active substances, and can be used for medicines for repairing damaged skin, healing wound surfaces and treating skin diseases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of medical technology, and specifically relates to a composition and a preparation method and application thereof. Background Art

[0002] Active substances include peptides and collagen. Peptides can be divided into single peptides, oligopeptides and polypeptides according to molecular weight. Collagen is a biological macromolecule, the main component of animal connective tissue, and the most abundant and widely distributed functional protein in mammals, accounting for 25%-30% of the total protein, and even up to 80% or more in some organisms. It is a family of proteins with multiple coding genes that can form a variety of collagen molecules.

[0003] In the prior art, most skin active ingredients are reducing ingredients and are unstable. Many active substances can only remain stable within a specific pH range. If the pH value of the system exceeds the stable range of the active substance, it may cause the active substance to decompose or deteriorate. Temperature and light are also important factors that affect the stability of active substances. The increase in temperature will accelerate the chemical reaction rate, thereby accelerating the degradation rate of active substances. Ultraviolet radiation will cause photodegradation reactions, causing the active substances to decompose or deteriorate.

[0004] The molecular structure of active substances is a key factor in determining their activity. For example, the triple helix structure of collagen is the basis of its biological activity, which gives collagen properties such as high tensile strength, biodegradability, and the ability to promote cell growth. If collagen loses its triple helix structure, its biological activity will disappear. However, there are still some problems and limitations in ensuring the activity of active ingredients in drugs. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a composition comprising cellulose and an active substance, wherein the Zeta potential or charging property of the active substance is opposite to that of the cellulose.

[0006] The inventors have found that by controlling the Zeta potential or charging properties of the active substance to be opposite to the Zeta potential or charging properties of the cellulose, the cellulose has appropriate flexibility / rigidity and network structure, can form strong electrostatic adsorption and / or hydrogen bonding and physical encapsulation with the active substance, stabilize the spatial structure of the active substance, achieve a sustained release effect, and can be used in medicines, etc.

[0007] In some embodiments, the cellulose forms a complex or composite with the active substance.

[0008] In some embodiments, the absolute value of the Zeta potential of the cellulose is 15-100 mV, preferably 20-60 mV, and more preferably 30-50 mV.

[0009] In some embodiments, the absolute value of the Zeta potential of the active substance is 10-100 mV, preferably 20-50 mV, and more preferably 30-40 mV.

[0010] In some embodiments, the sum of the absolute values ​​of the Zeta potential of the cellulose and the active substance is 25-200 mV, preferably 60-90 mV.

[0011] In some embodiments, the cellulose is nanocellulose, which has a diameter of less than 100 nanometers, preferably less than 50 nanometers, and more preferably 5-20 nanometers; In some embodiments, the cellulose is nanocellulose, and its aspect ratio is greater than 50, preferably greater than 100, and more preferably greater than 200.

[0012] In some embodiments, the cellulose is modified cellulose, which is modified by converting the hydroxyl groups in the cellulose into groups with positive or negative charge; preferably, the modified cellulose is obtained by replacing the hydroxyl groups in the cellulose with carboxymethyl, carboxyl, phosphoric acid or sulfonic acid groups to obtain a modified cellulose with a negative charge; and the modified cellulose is obtained by replacing the hydroxyl groups in the cellulose with quaternary ammonium groups to obtain a modified cellulose with a positive charge.

[0013] In some embodiments, the active substance is selected from biologically active proteins, such as keratin, silk protein, collagen or cell growth factor; biologically active peptides, including polypeptides, oligopeptides, cyclic peptides according to molecular weight and structure, and signal peptides, neurotransmitter inhibitory peptides, carrier peptides or enzyme inhibitory peptides according to function.

[0014] In some embodiments, the Zeta potential of the cellulose and the active substance is controlled by adjusting the pH values ​​of the cellulose and the active substance before mixing, and then the two are mixed to form a complex or a composite. In this way, the cellulose and the active substance can be tightly bound together, and even if the system pH value of the formed complex or composite is adjusted later, the tight bond between the cellulose and the active substance will not be destroyed.

[0015] In some embodiments, the Zeta potential of cellulose and active substances is controlled separately by adjusting the pH value, and the pH is adjusted in the range of 3-11, for example, the pH of cellulose and active substances is adjusted to 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 10.5, 11.

[0016] In some embodiments, in the composition, the mass ratio of the cellulose to the active substance is 1:100-1:10000, for example, 1:100, 1:500, 1:1000, 1:3000, 1:5000, 1:7000, 1:10000.

[0017] In some embodiments, the composition further comprises cellulase, and preferably the cellulase comprises at least one of endo-nase, exo-nase and glucosidase.

[0018] In some embodiments, in the composition, the added amount of the cellulase is 100-500 U / g, based on the absolute dry mass of cellulose.

[0019] In some embodiments, in the composition, the filter paper enzyme (FPA) activity of the cellulase is 30-60 U / mg, preferably 40-50 U / mg, such as 45 U / mg.

[0020] In some embodiments, the surface adsorption rate of cellulose in the composition to the active substance is: the adsorption rate after 5 hours of adsorption is 60% or more, preferably the adsorption rate is 70% or more, more preferably the adsorption rate is 90% or more; or the adsorption rate after 10 hours of adsorption is 85% or more, preferably the adsorption rate is 95% or more, more preferably the adsorption rate is 98% or more.

[0021] The present invention also provides a method for preparing the above-mentioned composition, which comprises: (S1) preparing a solution of the active substance; (S2) adding the cellulose solution to (S1) and mixing; preferably, mixing is performed by high-speed vortex oscillation; And also includes optional steps (S3), (S4): (S3) preparing a cellulase solution and refrigerating it for later use; (S4) Mixing the cellulase solution in step (S3) and the solution of the composition obtained in step (S2); preferably, mixing is performed by high-speed vortex oscillation.

[0022] In some embodiments, when the cellulose is modified cellulose, the method for preparing the composition further comprises preparing the modified cellulose: (SS1) converts the hydroxyl groups on the cellulose surface into groups with positive or negative charges; And also includes the optional step (SS2): (SS2) high pressure homogenization treatment performed after step (SS1); Preferably, in the step (SS1), the hydroxyl groups in the cellulose are replaced with carboxymethyl, carboxyl, phosphoric acid, or sulfonic acid groups to obtain negatively charged cellulose; and the hydroxyl groups in the cellulose are replaced with quaternary ammonium groups to obtain positively charged cellulose.

[0023] In some embodiments, the concentration of the active substance solution in step (S1) is 0.01-25 wt %, preferably 0.1-5 wt %, such as 1.0 wt %; In some embodiments, the step (S1) further includes adjusting the pH of the solution of the active substance after preparing it, and the pH range of the adjusted pH is between 3-11. The reagents used to adjust the pH include acid solutions, alkaline solutions or buffer solutions, commonly used acid solutions such as hydrochloric acid, sulfuric acid, acetic acid, etc., commonly used alkaline solutions such as sodium hydroxide, sodium bicarbonate, concentrated ammonia solution, etc., commonly used buffer solutions such as phosphate buffer, borate buffer, boric acid buffer, etc.

[0024] In some embodiments, the concentration of the cellulose solution in step (S2) is 0.01-25 wt %, preferably 0.1-5 wt %, such as 1.0 wt %; In some embodiments, the volume ratio of the active substance solution to the cellulose solution in step (S2) is 1:0.1-100, for example, the volume ratio is 1:1; In some embodiments, the step (S2) further comprises adjusting the pH of the cellulose solution before mixing, wherein the pH is adjusted in the range of 3-11, and the reagents used to adjust the pH include acid solutions, alkaline solutions or buffer solutions, commonly used acid solutions such as hydrochloric acid, sulfuric acid, acetic acid, etc., commonly used alkaline solutions such as sodium hydroxide, sodium bicarbonate, concentrated ammonia solution, etc., commonly used buffer solutions such as phosphate buffer, borate buffer, boric acid buffer, etc.

[0025] In some embodiments, step (S2) further comprises adjusting the pH of the formed complex or compound system after mixing, wherein the pH is adjusted to within the range of 5-11, for example, to 7.0 or 8.0; In some embodiments, the rotation speed of the high-speed vortex oscillation in step (S4) is 2000-3000 rpm, and the oscillation time is 5-10 minutes.

[0026] The present invention also provides the use of the above-mentioned composition in the preparation of medicines, such as the use of the composition in the preparation of medicines for repairing damaged skin, healing wounds or treating skin diseases.

[0027] The present invention also provides a method for repairing damaged skin, healing wounds or treating skin diseases, which comprises administering the above composition to a patient in need.

[0028] According to an embodiment of the present invention, the patient in need may be a mammal, such as a human, livestock or a pet.

[0029] The present invention also provides a medicine for repairing damaged skin, healing wounds or treating skin diseases, which comprises the above-mentioned composition.

[0030] In some embodiments, the drug product further contains one or more pharmaceutically acceptable excipients.

[0031] In some embodiments, the drug is applied to the skin and can be formulated as a topical preparation; suitable topical preparations include, but are not limited to, ointments, creams, lotions, pastes, aerosol sprays, roll-ons, or aerosol foam (mousse) compositions.

[0032] In some embodiments, the drug is applied to 3D printed artificial skin to promote the repair or healing of defects and wounds.

[0033] The present invention also provides the use of the above-mentioned composition in daily chemical products, foods, beverages, special medical formula foods or health products, such as cosmetics for hair care and skin care; and provides a skin care and hair care method, which comprises administering the above-mentioned composition to an individual in need.

[0034] The present invention also provides a cosmetic comprising the above composition.

[0035] In some embodiments, the cosmetic further contains cosmetic ingredients including fragrance, water, oil, surfactant, moisturizer, polyol, polymer, preservative, colorant, emollient, anti-wrinkle agent, antioxidant or whitening agent.

[0036] Beneficial Effects In the composition provided by the present invention, the active substance matches the cellulose Zeta potential, and the two are more tightly bound through strong electrostatic adsorption, hydrogen bonding and physical embedding, and can adapt to active substances of different structures. The composition forms a barrier between the active substance and the protease to protect it from protease cleavage, thereby playing a role in isolating external interference, and provides a new idea and method for protecting polypeptide active substances that are easily attacked by proteases. Further, by adjusting the pH values ​​of the cellulose and the active substance before mixing, the Zeta potential of the cellulose and the active substance is controlled, and then the two are mixed to obtain a composition, so that the cellulose and the active substance can be tightly bound to achieve protection of the active substance, thereby avoiding the subsequent complex or compound in different application systems. The damage to the structure and activity of the active substance itself is avoided by the change of pH value.

[0037] In the composition provided by the present invention, cellulose can also be degraded by adding cellulase, causing the cellulose network structure to collapse, thereby releasing active substances adsorbed on the cellulose surface or embedded in the network structure.

[0038] Compared with the existing recombinant collagen technology, the composition provided by the present invention is safer and more effective, has a simple preparation process, low cost, and is easy to mass produce, which is of great significance for promoting the industrialization of pharmaceutical technologies. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 is the relationship between the adsorption rate and adsorption time of the nanocellulose surface in Example 1; Figure 2 The relationship between keratin stability and adsorption time after adding nanocellulose in Example 1; Figure 3 This is a scanning microscope image of the hair scales repaired with nanocellulose in Example 7. DETAILED DESCRIPTION

[0040] [Cellulose] The cellulose involved in the present invention is a polysaccharide structure composed of hundreds to thousands of glucose units, and is a linear high molecular polymer formed by connecting glucose molecules through β-1,4-glycosidic bonds.

[0041] In some embodiments, the absolute value of the cellulose Zeta potential is 15-100 mV, preferably 20-60 mV, and further preferably 30-50 mV. For example, under the condition of pH 7.0, the absolute value of the cellulose Zeta potential is 30 mV, 32 mV, 34 mV, 36 mV, 38 mV, 39 mV, 40 mV, 41 mV, 42 mV, 43 mV, 44 mV, 45 mV, 46 mV, 47 mV, 48 mV, 49 mV, and 50 mV.

[0042] In some embodiments, the Zeta potential of cellulose is controlled by adjusting the pH value of the system, and the pH is adjusted in the range of 3-11; for example, at pH 7.0, the Zeta potential of modified cellulose with a negative charge obtained by replacing the hydroxyl groups in cellulose with carboxymethyl or carboxyl groups is -60 mV to -20 mV, and the Zeta potential of the cellulose is adjusted to be -50 mV to -10 mV when the pH is adjusted to be 3.0-5.0; the Zeta potential of modified cellulose with a positive charge obtained by replacing the hydroxyl groups in cellulose with quaternary ammonium groups is +20 mV to +60 mV at pH 7.0, and the Zeta potential of the cellulose is adjusted to be +10 mV to +50 mV when the pH is adjusted to be 8.0-11.0.

[0043] [Nanocellulose] The nanocellulose involved in the present invention is a nanometer-scale fiber made by treating cellulose by chemical, physical, or combined methods. The diameter is usually between a few nanometers and a few hundred nanometers, and the length can reach hundreds of nanometers to a few microns. It has a high specific surface area and good biocompatibility.

[0044] In some embodiments, the diameter of the nanocellulose is less than 100 nanometers, preferably less than 50 nanometers, and more preferably 5-20 nanometers.

[0045] In some embodiments, the specific surface area of ​​the nanocellulose is greater than 100 m 2 / g, preferably greater than 200 m 2 / g, more preferably greater than 300m 2 / g.

[0046] [Modified cellulose] The modified cellulose of the present invention is modified by converting the hydroxyl groups in the cellulose into groups with positive or negative charges. For example, the modified cellulose is obtained by replacing the hydroxyl groups in the cellulose with carboxymethyl, carboxyl, phosphoric acid or sulfonic acid groups to obtain a negatively charged modified cellulose; and the modified cellulose is obtained by replacing the hydroxyl groups in the cellulose with quaternary ammonium groups to obtain a positively charged modified cellulose.

[0047] In some embodiments, 1% to 80% of the hydroxyl groups in the modified cellulose are substituted with carboxymethyl, carboxyl, phosphoric acid, sulfonic acid or quaternary ammonium groups.

[0048] In some embodiments, the crystallinity of the modified cellulose is lower than 90%, preferably lower than 85%, and more preferably the crystallinity of the modified cellulose is 60-85%.

[0049] In some embodiments, the surface charge of the modified cellulose is greater than 0.5 mmol / g, such as greater than 1 mmol / g, greater than 1.2 mmol / g, or greater than 1.5 mmol / g.

[0050] [Cellulose with positive or negative charge] The cellulose with positive or negative charge involved in the present invention is cellulose with controllable surface charge characteristics achieved by introducing carboxyl, carboxymethyl, phosphoric acid, sulfonic acid or quaternary ammonium groups through surface modification.

[0051] By substituting the hydroxyl groups in cellulose with carboxymethyl, carboxyl, phosphoric acid or sulfonic acid groups, cellulose with a negative charge is obtained; by substituting the hydroxyl groups in cellulose with quaternary ammonium groups, cellulose with a positive charge is obtained.

[0052] [Source of cellulose raw materials] The raw material source of the cellulose involved in the present invention includes at least one of natural cellulose, regenerated cellulose and bacterial cellulose, for example, cellulose extracted from cotton, seaweed, hemp, bamboo, tree, wood, grain, bean, plant straw, cellulose based on bacterial fermentation, etc. The raw material source of the cellulose involved in the present invention also includes microcrystalline cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, microcrystalline cellulose, methyl cellulose. Preferably, the raw material source of the cellulose is cellulose fiber with a degree of polymerization of 700-1200, and more preferably cellulose fiber with a degree of polymerization of 800-1000.

[0053] [Active substances] The active substance involved in the present invention is selected from biologically active proteins, such as keratin (e.g., α-keratin, β-keratin), elastin (e.g., tropoelastin, etc.), fibrillin (e.g., fibrillin-1 (the main component of microfibrils), fibrillin-2 (component of elasticity), fibrillin-3 (present in the brain), fibrillin-4 (component of elasticity), etc.), fibrinogen / fibrin / thrombin (e.g., fibrinogen is converted into fibrin by thrombin during wound healing), fibronectin, laminin, silk protein, collagen (e.g., collagen I present in skin, tendon and bone, collagen II present in cartilage or collagen III present in connective tissue, collagen IV present in extracellular matrix protein, collagen V present in hair, etc.), from a wide range of sources. Collagen extracted from raw materials (such as pig, cow, human, fish or rat tail, etc.), such as human recombinant collagen (recombinant collagen type III or type XVII), transgenic human tissue collagen, porcine collagen, human placental collagen, bovine collagen, autologous collagen, collagen fibers and human tissue collagen matrix, cell growth factors (fibroblast growth factor, endothelial growth factor or insulin-like growth factor); bioactive peptides, including polypeptides, oligopeptides, cyclic peptides according to molecular weight and structure, and signal peptides, neurotransmitter inhibitory peptides, carrier peptides or enzyme inhibitory peptides according to function (oligopeptide-1, tripeptide-1, hexapeptide-1, hexapeptide-3, acetyl oligopeptide, palmitoyl oligopeptide, carnosine, glutathione or blue copper peptide); non-colloidal active small molecule compounds, such as dasatinib, quercetin, fisetin, epigallocatechin gallate, proanthocyanidin C1, hydroquinone, arbutin, kojic acid, phenethylresorcinol or niacinamide.

[0054] In some embodiments, when the active substance has a Zeta potential, the absolute value of the Zeta potential of the active substance is 10-100 mV, preferably 20-50 mV, and further preferably 30-40 mV, for example, 26 mV, 29 mV, 30 mV, 31 mV, 32 mV, 33 mV, 34 mV, 35 mV, 36 mV, 37 mV, 38 mV, 39 mV, and 40 mV.

[0055] In some embodiments, the Zeta potential of the active substance is controlled by adjusting the pH value of the system, and the pH is adjusted in the range of 3-11; for example, the isoelectric point of collagen is 7.5-7.8, and the pH is adjusted in the range of 5.0-11.0, and the Zeta potential of collagen is in the range of +45 mV to -30 mV; the isoelectric point of blue copper peptide is 10.0, and the pH is adjusted in the range of 5.0-11.0, and the Zeta potential of blue copper peptide is in the range of +35 mV to -15 mV; the isoelectric point of fibroblast growth factor is 9.6, and the pH is adjusted in the range of 5.0-11.0, and the Zeta potential of fibroblast growth is in the range of +37 mV to -10 mV.

[0056] In some embodiments, the active substance is selected from non-colloidal active small molecule compounds, and the ionization or hydrolysis equilibrium of the non-colloidal active small molecule compounds is controlled by adjusting the pH value of the system; for example, the niacinamide solution itself is relatively stable between pH 5-7, and the pH is adjusted within the range of 5.0-7.0 to control the ionization or hydrolysis of niacinamide to prevent excessive hydrolysis into niacin and skin irritation; quercetin is relatively stable between pH 5-8, and the pH is adjusted within the range of 5.0-8.0 to control quercetin self-oxidation to prevent the loss of quercetin's free radical scavenging activity.

[0057] [Introduction of carboxyl groups into cellulose surface hydroxyl groups] The present invention relates to the introduction of carboxyl groups into cellulose surface hydroxyl groups, including but not limited to one or more of TEMPO (tetramethylpiperidinium oxide) oxidation method, H2O2 oxidation method, HIO4 oxidation method, NaClO2 oxidation method, etc.; more preferably, surface carboxylated nanocellulose prepared by TEMPO oxidation method. Further preferably, the TEMPO oxidation method comprises dispersing cellulose fibers in an aqueous solution of TEMPO and NaBr, adding NaClO to carry out oxidation reaction for 6-12 hours, and maintaining the system alkaline by dripping an alkaline solution during the reaction, such as dripping potassium hydroxide, sodium hydroxide, potassium carbonate or sodium carbonate solution to maintain the pH at 10.0-10.5.

[0058] [Introduction of carboxymethyl groups into hydroxyl groups on the surface of cellulose] The present invention relates to the introduction of carboxymethyl groups into cellulose surface hydroxyl groups, including but not limited to the alkalization-etherification method. More preferably, the alkalization is carried out using an aqueous solution of an organic base or an inorganic base. The organic base or inorganic base is, for example, sodium hydroxide, potassium hydroxide, calcium hydroxide, carbon carbonate, potassium carbonate, triethylamine, ammonia water, etc. The etherification is carried out using sodium chloroacetate or chloroacetic acid, for example, the etherification is carried out using a methanol or ethanol solution of sodium chloroacetate. Wherein, the alkalization is carried out at 10-50°C for 10-60 minutes, preferably at 25°C for 30 minutes; the etherification is reacted at 50-100°C for 30-150 minutes, preferably at 60-80°C for 60-120 minutes.

[0059] [Introduction of quaternary ammonium groups into hydroxyl groups on the surface of cellulose] The present invention relates to the introduction of quaternary ammonium groups into hydroxyl groups on the surface of cellulose, including but not limited to the substitution reaction of quaternary ammonium reagents with cellulose under alkaline conditions. More preferably, the quaternary ammonium reagent is selected from one or more of 3-chloro-2-hydroxypropyltrimethylammonium chloride, 2,3-epoxypropyltrimethylammonium chloride, 3-chloro-2-hydroxypropyltrimethylammonium bromide, and 2,3-epoxypropyltrimethylammonium bromide. Further preferably, the reaction temperature for introducing quaternary ammonium groups is 50-100°C, such as 65°C.

[0060] [Introduction of phosphoric acid groups into hydroxyl groups on the surface of cellulose] The present invention relates to the introduction of phosphoric acid groups into cellulose surface hydroxyl groups, including but not limited to reacting hydroxyl groups on the surface of cellulose with a phosphorylation reagent. More preferably, the phosphorylation reagent includes diammonium hydrogen phosphate or a mixture of diammonium hydrogen phosphate and urea. The method includes, for example, impregnating cellulose with a phosphorylation reagent (according to a mass ratio of cellulose: diammonium hydrogen phosphate: urea of ​​1:0.8:3.7) for 1 hour, and then transferring the mixture to a 170°C oven to continue reacting for 30 minutes.

[0061] [Introduction of sulfonic acid groups into hydroxyl groups on the surface of cellulose] The present invention relates to the introduction of sulfonic acid groups into cellulose surface hydroxyl groups, including but not limited to reacting hydroxyl groups on the cellulose surface with a sulfonating agent. More preferably, the reaction includes hydrolyzing the amorphous region of cellulose fibers at 45° C. using 64% sulfuric acid, while simultaneously inserting sulfonic acid groups on the surface of the cellulose crystalline region through an esterification reaction for 60 minutes.

[0062] [Cellulose pretreatment and post-treatment] Before introducing carboxyl, carboxymethyl, phosphoric acid, sulfonic acid or quaternary ammonium groups, the method of the present invention may further include a step of pretreating cellulose. Preferably, the pretreatment includes pretreating cellulose with alkali and acid. Further preferably, the cellulose is dispersed with an alkali solution, heated, washed with water until neutral, and then dispersed with an acid solution, heated, and washed with water until neutral.

[0063] Preferably, in the step of pretreating cellulose, the alkali includes organic alkali and inorganic alkali, such as sodium hydroxide, potassium hydroxide, calcium hydroxide, carbon carbonate, potassium carbonate, triethylamine, ammonia water, etc.; the acid includes organic acid and inorganic acid, such as hydrochloric acid, sulfuric acid, phosphoric acid, formic acid, acetic acid, citric acid, etc. When pretreating cellulose with alkali and acid, alkali solution or acid solution is added to cellulose and the pulp concentration is adjusted to 0.1-10wt%, preferably 2.5wt%.

[0064] Preferably, in the step of pretreating cellulose, the heating treatment temperature is 100-150° C., and the time is 10-60 minutes; preferably, the heating treatment temperature is 120-130° C., and the time is 30 minutes.

[0065] After the reaction of introducing carboxyl, carboxymethyl, phosphoric acid, sulfonic acid or quaternary ammonium groups is completed, the method of the present invention may further optionally include a post-treatment step. Preferably, the post-treatment step includes adjusting the pH to neutral, washing the reaction product with water, and filtering until the conductivity of the filtrate is less than 50 μS / cm, preferably until the conductivity of the filtrate is less than 5 μS / cm.

[0066] [High-pressure homogenization] The high-pressure homogenization treatment of the present invention refers to a process of uniformly mixing the components in a substance by applying high pressure to form a homogeneous system. The high-pressure homogenization treatment of the present invention may include adjusting the concentration of the cellulose fiber obtained in step (S1) to 1wt% with water, pre-shearing and dispersing the fiber with a disperser at 2000rpm for 5 minutes, and then high-pressure homogenization treatment at a pressure of 200-1200bar.

[0067] [Sum of the absolute values ​​of the Zeta potential of cellulose and active substances] The sum of the absolute values ​​of the Zeta potential of cellulose and the active substance involved in the present invention refers to the sum of the absolute values ​​of the Zeta potential of the cellulose and the active substance when the cellulose and the active substance carry opposite charges.

[0068] [Cellulase] The cellulase involved in the present invention refers to an enzyme that can degrade cellulose to generate glucose, including at least one of endo-enzyme, exo-enzyme and glucosidase, such as composite cellulase derived from Trichoderma reesei.

[0069] [Flexibility / rigidity of cellulose] The cellulose flexibility involved in the present invention refers to cellulose with a crystallinity of 60-85%, or an aspect ratio higher than 250, or a Zeta potential absolute value higher than 40 mV, which has relatively strong flexibility.

[0070] The cellulose rigidity involved in the present invention means that the cellulose rigidity is relatively strong when the cellulose crystallinity is above 85%, or the aspect ratio is lower than 150, or the absolute value of the Zeta potential is lower than 30 mV.

[0071] [Daily Chemicals] The daily chemical products involved in the present invention refer to chemical products that are processed and manufactured with certain chemicals or natural products as raw materials, are related to people's daily lives, and are used to clean and beautify people's home life and meet the health, cleanliness, beauty and comfort needs of animals or pets. According to the purpose, they can be divided into toiletries, household products, kitchen and bathroom products, decorative products, cosmetics, animal or pet care products, etc., and according to industrial practices, they can be divided into cosmetics (such as skin care cosmetics, beauty cosmetics, cleaning cosmetics, hair cosmetics), washing products (such as soaps, washing powder, detergents), oral products (such as toothpaste, mouthwash), fragrances, deodorants, insect repellents and pest control products, animal or pet care products (such as pet-specific bathing and cleaning products, oral care products, insect repellent and flea prevention products, skin care products), etc.

[0072] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0073] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0074] Unless otherwise specified, % in the following preparation examples and embodiments refers to mass percentage.

[0075] Zeta potential test method of modified nanocellulose: Take the prepared modified nanocellulose, dilute it with ultrapure water to 0.05% solid content, and use a Zeta potential analyzer to detect the Zeta potential of the modified nanocellulose.

[0076] Zeta potential test method for active substances: Use ultrapure water to prepare an active substance solution with a solid content of 0.01%, and use a Zeta potential analyzer to detect its Zeta potential.

[0077] Crystallinity test method: Take the prepared modified nanocellulose, freeze-dry it at -50°C and vacuum degree 0.01 mbar for 72 hours, use an X-ray diffractometer to scan at 5-40 degrees, analyze the sample X-ray diffraction pattern, and calculate the sample crystallinity.

[0078] Diameter and aspect ratio test method: Take the prepared modified nanocellulose, dilute it with ultrapure water to 0.01% solid content, ultrasonically disperse it for 10 minutes, drop it onto a copper mesh and air-dry it, then use a transmission electron microscope to take a picture of the modified nanocellulose morphology at a magnification of 10,000-20,000. Use ImageJ software to measure and count the length and diameter of the modified nanofibers and calculate the aspect ratio.

[0079] Specific surface area test method: Take 1% modified nanocellulose sample and place it in a centrifuge tube, immerse it in liquid nitrogen for rapid freezing, transfer it to -50 degrees Celsius, freeze-dry the sample under vacuum conditions of 0.05 mbar for 72 hours, and use a specific surface area analyzer to detect the specific surface area of ​​the sample.

[0080] Test method for surface charge of modified cellulose: Take 5 g of 1% modified nanocellulose, dilute it to 0.1% with deionized water, add 2 ml of 0.1 M HCl and 1 ml of 50 mM sodium chloride solution, and stir at room temperature for 30 minutes. Use 0.1 M NaOH to titrate and monitor the conductivity and pH value of the suspension, titrate to pH 11, and calculate the charge of the anionic groups on the cellulose surface (including the introduction of carboxyl, carboxymethyl, and sulfonic acid groups) through the titration curve.

[0081] Take 5 g of 1% modified nanocellulose, dilute it to 0.1% with deionized water, use 0.01 M AgNO3 to titrate and monitor the conductivity of the suspension, titrate until the conductivity value continues to increase steadily, and calculate the charge of the cationic quaternary ammonium salt group on the cellulose surface through the titration curve.

[0082] Adsorption rate test method: Weigh the active substance to be adsorbed and dissolve or disperse it in deionized water. For active substances with characteristic ultraviolet absorption wavelengths, use an ultraviolet spectrophotometer to establish a working curve between the concentration of the active substance and the absorbance value. For active substances without characteristic ultraviolet absorption, use high performance liquid chromatography or corresponding enzyme-linked immunosorbent assay kits to establish a working curve between the concentration of the active substance and the detection response value.

[0083] Weigh cellulose, adjust the solid content to 0.1% with deionized water, add active substances, shake and mix, incubate for a certain period of time, centrifuge at 10,000 rpm for 15 minutes, and filter with a 0.2 μm filter membrane. Use a UV spectrophotometer, high performance liquid chromatography or corresponding enzyme-linked immunosorbent assay kit to detect the concentration of free active substances, and then calculate the content of active substances adsorbed on the cellulose surface.

[0084] Absorbance calibration curve establishment: (1) Dissolve keratin in deionized water to form a keratin solution with a concentration of 0.01%, and scan the entire wavelength to determine the maximum absorption wavelength; (2) Gradient dilution of the keratin solution, measure the absorbance at the wavelength of maximum absorption, and establish a concentration-absorbance standard curve.

[0085] Preparation Example 1: Preparation of TJ-300: Use 0.1M NaOH solution to disperse cellulose fibers with a degree of polymerization of 800-1000, a cellulose alpha content of >90%, and a whiteness of >85% ISO, keep the slurry concentration at 2.5%, heat at 121°C for 30 minutes, and wash and filter with sterile water until the filtrate pH is neutral. Then use 0.3 M HCl solution to disperse the slurry, adjust the slurry concentration to 2.5%, heat at 121°C for 30 minutes, and wash and filter with sterile water until the filtrate pH is neutral.

[0086] Weigh the cellulose fiber with an absolute dry mass of (5.0 ± 0.1) g after the above pretreatment, knead and mix with (15 ± 0.1) g, 30% NaOH alkaline solution at 25°C, and soak for 30 min. After the soaking, add (7 ± 0.1) g dispersion of sodium chloroacetate dispersed with 100 mL 95% ethanol and preheated to 70°C, and stir at 500 rpm in a constant temperature water bath at 60-80°C for 30-120 minutes. After the reaction, adjust the pH to neutral with glacial acetic acid, wash the reaction product repeatedly with ultrapure water and filter it with an ultrafiltration system until the conductivity of the filtrate is less than 5 μS / cm. Adjust the concentration of the cellulose fiber after the reaction to 1% with sterile water and homogenize it in a sterile room with a high-pressure homogenizer at 200, 400, 600, 800, 1000, 1200 bar in sequence, and store it in a 4°C refrigerator for standby use.

[0087] In this preparation example, by adjusting the etherification reaction temperature and time (60°C, 30 minutes; 70°C, 100 minutes; 80°C, 120 minutes), the prepared TJ-300 has high flexibility. The characterization results obtained by testing and calculation are shown in Table 1: Table 1: Characterization results of TJ-300 prepared at different etherification reaction temperatures and times

[0088] Preparation Example 2: Preparation of TJ-321T Use 0.1M NaOH solution to disperse cellulose fibers with a degree of polymerization of 800-1000, a cellulose alpha content of >90%, and a whiteness of >85% ISO, keep the slurry concentration at 2.5%, heat at 121°C for 30 minutes, and wash and filter with sterile water until the filtrate pH is neutral. Then use 0.3 M HCl solution to disperse the slurry, adjust the slurry concentration to 2.5%, heat at 121°C for 30 minutes, and wash and filter with sterile water until the filtrate pH is neutral.

[0089] Weigh the cellulose fiber with an absolute dry mass of (10.0 ± 0.1) g after the above pretreatment, disperse it in a solution containing 1.6 ± 0.1 g TEMPO and 1.0 ± 0.1 g NaBr at 25 °C, stir continuously at 500 rpm and drop 75 ml 10% NaClO to start the oxidation reaction for 6-12 hours. During the reaction, monitor and maintain the pH of the reaction suspension at 10.0 by dropping 0.5 M NaOH solution. After the reaction, adjust the pH to neutral with 1.0 M HCl, wash the reaction product repeatedly with ultrapure water and filter it with an ultrafiltration system until the conductivity of the filtrate is less than 5 μS / cm. Adjust the concentration of the oxidized cellulose fiber to 1% with sterile water and homogenize it in a sterile room with a high-pressure homogenizer at 200, 400, 600, 800, 1000, 1200 bar in sequence, and store it in a 4 °C refrigerator for later use.

[0090] In this preparation example, TJ-321T obtained by adjusting the TEMPO catalytic oxidation time (6h; 8h; 12h) has moderate flexibility. After testing and calculation, the characterization results are shown in Table 2.

[0091] Table 2: Characterization results of TJ-321T prepared under different TEMPO catalytic oxidation times

[0092] Preparation Example 3: QCNF Preparation Use 0.1M NaOH solution to disperse cellulose fibers with a degree of polymerization of 800-1000, a cellulose alpha content of >90%, and a whiteness of >85% ISO, keep the slurry concentration at 2.5%, heat at 121°C for 30 minutes, and wash and filter with sterile water until the filtrate pH is neutral. Then use 0.3 M HCl solution to disperse the slurry, adjust the slurry concentration to 2.5%, heat at 121°C for 30 minutes, and wash and filter with sterile water until the filtrate pH is neutral.

[0093] Weigh the cellulose fiber with an absolute dry mass of (15.0 ± 0.1) g after the above pretreatment, disperse it in 200 ml of 5% NaOH solution at room temperature, and stir and immerse for 30 minutes. After the immersion, add 7.5 to 10 grams of 2,3-epoxypropyltrimethylammonium chloride, heat to 65°C, and stir at 500rpm for 1-8 hours. After the reaction, adjust the pH to neutral with 1.0 M HCl, wash the reaction product repeatedly with ultrapure water and filter it with an ultrafiltration system until the conductivity of the filtrate is less than 5 μS / cm. Adjust the concentration of the reacted cellulose fiber to 1% with sterile water and homogenize it in a sterile room with a high-pressure homogenizer at 200, 400, 600, 800, 1000, and 1200 bar in sequence, and store it in a 4°C refrigerator for standby use.

[0094] In this preparation example, the QCNF obtained by adjusting the amount of etherifying agent and the reaction time (7.5g, 1h; 8.5g, 6h; 10g, 8h) has a certain rigidity (+15 / +46 mV) or flexibility (+79 mV). After testing and calculation, the characterization results are shown in Table 3 Table 3: Characterization results of QCNF prepared at different etherifying agent dosages and reaction times

[0095] Example 1: Adsorption and stability of keratin on the surface of nanocellulose (1) Select TJ-300 (Zeta potential -49 mV at pH 7.0), TJ-321T (Zeta potential -47 mV at pH 7.0), and QCNF (Zeta potential +15 / +46 / +79 mV at pH 7.0) nanocellulose prepared in Preparation Example 1-3, adjust the solid content to 0.1%, add keratin solution (10 mg / mL, Zeta potential -26 mV at pH 7.0), wherein the volume ratio of keratin solution to nanocellulose prepared in Preparation Example 1-3 is 1:1, shake and mix, and incubate at 37°C for 0 to 24 hours.

[0096] (2) Take samples at six time points: 0h, 2h, 4h, 6h, 8h, 12h, and 24h, centrifuge (10000 rpm, 15min), and filter through a 0.2μm filter membrane.

[0097] (3) Set an equal volume of deionized water as a control, measure the absorbance of the filtrate, and calculate the adsorption rate of keratin on the nanocellulose surface based on the concentration-absorbance curve. The relationship between the adsorption rate of keratin on the surface of TJ-300, TJ-321T, and QCNF nanocellulose and the adsorption time is shown in the following figure: Figure 1 shown.

[0098] (4) After 24 h of adsorption stabilization in the nanocellulose-keratin complex in (1), keratinase (50 IU / g) was added and incubated at 37 °C for 0 to 24 h.

[0099] (5) Samples were taken at six time points: 0h, 2h, 4h, 6h, 8h, 12h, and 24h. The keratin content in the samples was quantified using a keratin ELISA test kit. The keratin content in the samples at the 0h time point was used as a control to calculate the keratin stability after adding nanocellulose. The results are as follows: Figure 2 shown.

[0100] Example 2: Preparation of collagen-nanocellulose composite and experiment on stabilization and protection of collagen by nanocellulose (1) Prepare collagen at a concentration of 1.0 wt%, including recombinant collagen type III (Zeta potential -29 mV at pH 7.0) and type XVII (Zeta potential -31 mV at pH 7.0), and refrigerate at 4°C until use.

[0101] (2) Pure water and 1% QCNF (Zeta potential +46 mV at pH 7.0) nanocellulose obtained in Preparation Example 1 were used to dilute collagen until the effective concentration of collagen in the solution was 0.1%. The mixture was incubated at 25°C and 60°C for 1 hour, and then cooled to room temperature.

[0102] (3) Using a circular dichroism spectrometer, the ellipticity was scanned in the wavelength range of 190-260 nm at a speed of 1 nm / s. The maximum positive absorption and negative absorption peaks of the ellipticity of each sample were recorded. The results are shown in Table 4 (Col-III represents type III recombinant collagen, Col-XVII represents type XVII recombinant collagen, Col-III-QCNF represents a complex of type III recombinant collagen and QCNF, and Col-XVII-QCNF represents a complex of type XVII recombinant collagen and QCNF).

[0103] Table 4: Maximum positive and negative absorption peaks of sample ellipticity

[0104] According to Table 4, at 25°C, the circular dichroism ellipticity of type III and type XVII recombinant collagen (Col-III, 25°C and Col-XVII, 25°C) has maximum positive absorption peaks at 224-225 nm and 220 nm, respectively, and maximum negative absorption peaks at 192-194 nm and 197-198 nm. According to the absorption peaks, it can be determined that type III and type XVII recombinant collagen have a triple helix structure. After incubation at 60°C for 1 hour, the maximum positive absorption peak of the circular dichroism ellipticity of type III and type XVII recombinant collagen (Col-III, 60°C and Col-XVII, 60°C) disappeared, indicating that the triple helix structure of collagen was destroyed. After incubation of type III and type XVII recombinant collagen and QCNF complexes (Col-III-QCNF and Col-XVII-QCNF) at 60°C for 1 hour, the circular dichroism ellipticity with the maximum positive absorption peak at 220 nm and the maximum negative absorption peak at 197 nm were retained, indicating that collagen did not lose its triple helical structure under the protection of QCNF.

[0105] Example 3: Wound healing experiment Take 2 ml of the type III recombinant collagen and QCNF complex (Col-III-QCNF) in Example 2 and spread it in a 6-well plate. Cut a 20 mm × 20 mm medical gauze, soak it in Col-III-QCNF, incubate it at 4 degrees Celsius for 24 hours, take it out and place it in a sterile culture dish, and sterilize it by ultraviolet irradiation for 15 minutes, which is the experimental group. The QCNF nanocellulose impregnated gauze prepared under the same conditions was used as a blank control, the untreated medical gauze was used as a negative control, and the commercial collagen wound dressing (3MPromogran Prisma) was used as a positive control. The full-thickness skin defect (8 mm in diameter) on the back of SPF SD rats (SPF SD rats were purchased from the Animal Experimental Research Center of Jiangsu University, 5-6 weeks old, 20 males, about 220-240 grams, and were evenly divided into 4 groups) was covered for treatment to evaluate the effect of the material on promoting skin wound healing. The dressings were changed and the wound diameters were measured on the 3rd, 7th, 14th and 21st days after surgery, and the wound healing rate was calculated. The results are shown in Table 5.

[0106] Table 5: Collagen-nanocellulose QCNF composite impregnated gauze promotes wound healing rate (%)

[0107] Example 4: Composite cellulase sustained release experiment (1) Prepare 1.0 wt% recombinant human collagen solution (Zeta potential of +35 mV at pH 7.0, pH 7.0) and composite cellulase solution (the composite cellulase is a commercial composite cellulase purchased from Shanghai Yuanye Biotechnology Co., Ltd., containing endo-nase, exo-nase, glucosidase, and filter paper enzyme activity FPA of 45 U / mg protein), and refrigerate at 4°C for use.

[0108] (2) The collagen solution prepared in (1) was mixed with 1% TJ-300 (Zeta potential -49 mV at pH 7.0) nanocellulose obtained in Preparation Example 1 or 1% QCNF (Zeta potential +46 mV at pH 7.0) nanocellulose obtained in Preparation Example 3 at a volume ratio of 1:100 (pH 7.0). After mixing, the mixture was vortexed at high speed (2000-3000 rpm) for 5-10 minutes to obtain a collagen-nanocellulose composite, which was then refrigerated at 4°C for later use.

[0109] (3) Take the composite cellulase solution prepared in (1) and add it to the collagen-nanocellulose composite prepared in (2) at an enzyme dosage of 100-500 U / g cellulose absolute dry mass. After mixing, vortex oscillate at high speed (2000-3000 rpm) for 1 minute to obtain a nanocellulose degradation composite loaded with collagen, which is then refrigerated at 4°C for later use.

[0110] (4) The complex prepared in (3) was loaded into a 96-well plate and placed in a 37°C constant temperature incubator for complex degradation and collagen release monitoring. Samples were taken at different degradation time points (0, 1, 2, 4, 8, 16, and 24 h), centrifuged at 5000 rpm, and the supernatant was collected. The enzyme-linked immunosorbent assay was used to quantitatively detect the release of collagen, and the DNS colorimetric method was used to detect the amount of free glucose produced by cellulase degradation of TJ-300 and QCNF.

[0111] (5) The complex prepared in (3) was placed in a 50 ml centrifuge tube and placed in a 37°C constant temperature incubator for complex degradation and complex viscosity monitoring. Samples were taken out at different degradation time points (0, 1, 2, 4, 8, 16, 24 h) and cooled to room temperature. The viscosity of the complex was measured using a rotational viscometer with a 4# rotor at a speed of 12 rpm to characterize the enzymatic degradation of the nanocellulose gel network.

[0112] Among them, the enzyme degradation test results are shown in Tables 6 and 7.

[0113] Table 6 Enzyme degradation test results of TJ-300 nanocellulose degradation complex loaded with collagen

[0114] The isoelectric point PI of recombinant human collagen is 8.0-9.0. Under neutral conditions, the Zeta potential of recombinant human collagen is +35 mV. It can be adsorbed on the negatively charged surface of TJ-300 (Zeta potential -49 mV). The sum of the absolute values ​​of the Zeta potential of TJ-300 and recombinant human collagen is 84 mV.

[0115] According to Table 6, with the increase of cellulase dosage and degradation time, the cumulative release of collagen and glucose increased, and the viscosity of the complex decreased. When the amount of cellulase added reached 500U / g, the cumulative release of collagen reached more than 50% after the degradation time exceeded 4h, and the cumulative release of glucose reached more than 10mg, indicating that the nanocellulose network structure collapsed and the collagen adsorbed on the surface or embedded in the network structure could be effectively released.

[0116] Table 7 Enzyme degradation test results of QCNF nanocellulose degradation complex loaded with collagen

[0117] At pH 7.0, the Zeta potentials of QCNF and recombinant human collagen were +46mV and +35mV, respectively. Since the surfaces of the two have the same charge, the adsorption of collagen on the surface of QCNF is hindered by electrostatic repulsion, and part of it exists in the solution in a free form (about 27%), and part of it is embedded in the QCNF network by hydrogen bonding and physical embedding. Some collagen or QCNF forms floccules with the added surface negatively charged cellulase (Zeta potential -28mv), resulting in a low overall viscosity of the complex and poor cellulase degradation ability.

[0118] Example 5: Single cellulase sustained release experiment This example refers to Example 4, with the only difference being that in step (1), the composite cellulase is replaced by single cellulases of endo-, exo- and glucosidase, respectively; in step (2), 1% TJ-300 (Zeta potential -49 mV at pH 7.0) nanocellulose obtained in Preparation Example 1 is mixed with the collagen solution; in step (3), an enzyme dosage of 500 U / g cellulose absolute dry mass is added to the collagen-nanocellulose composite prepared in step (2); the cumulative collagen release amount, the cumulative glucose release amount and the composite viscosity for 24 hours are detected; and the remaining steps are consistent with Example 4.

[0119] The test results showed that after adding endo-enzyme, exo-enzyme and glucosidase to hydrolyze TJ-300 and collagen complex for 24 hours, the cumulative release of collagen, the cumulative release of glucose and the viscosity of the complex were: endo-enzyme: 53%, 3.5 mg, 9920 mP s; exo-enzyme: 16%, 0.52 mg, 13010 mP s; glucosidase: 8%, 0.22 mg, 14370 mP s.

[0120] Example 6: Preparation of fibronectin-nanocellulose composite and the effect of pH on the composite (1) Prepare a 1 mg / ml fibronectin solution using a pH 7.0, 50 mM Tris buffer solution (the fibronectin was purchased from Sigma, with an isoelectric point of 5.5 and a Zeta potential of -30 mV at pH 7.0). Use 0.1 M HCl to adjust the pH to 4.5, at which the Zeta potential of fibronectin is +25 mV; (2) Take 1% TJ-300 (Zeta potential -49 mV at pH 7.0) prepared in Preparation Example 1 and adjust the pH to 4.5 using 0.1 M HCl. Under this pH condition, the Zeta potential of TJ-300 is -37 mV.

[0121] (3) The fibronectin solution was mixed with TJ-300 at a mass ratio of 1:100, and the mixture was vortexed at a high speed (2000-3000 rpm) for 5-10 minutes to obtain a solution containing a fibronectin-nanocellulose complex. The pH of the complex solution was adjusted to 7.0 using 0.1 M NaOH.

[0122] (4) Take the fibronectin-nanocellulose complex solution prepared in step (3), centrifuge it at 10,000 rpm for 10 minutes, take the supernatant, and detect the free fibronectin content.

[0123] (5) Take the unadjusted pH fibronectin solution (Zeta potential -30 mV at pH 7.0) and TJ-300 (Zeta potential -49 mV at pH 7.0) from steps (1) and (2), and follow the procedures of steps (3) and (4) to detect the free fibronectin content.

[0124] The test results show that adjusting the system pH to below the isoelectric point of fibronectin before preparing the fibronectin-nanocellulose complex can cause the fibronectin Zeta potential to change from negative to positive, thereby enhancing the binding with negatively charged nanocellulose. After the two form a complex, the system pH is adjusted to neutral again, and only a small amount (<5%) of fibronectin is free in the supernatant. On the contrary, the system pH was not adjusted before the fibronectin-nanocellulose complex was prepared. In the complex formed by the two, nanocellulose can only provide physical coating protection, and the two are loosely bound. More than 35% of fibronectin was detected to be free in the supernatant.

[0125] Example 7: Preparation of keratin-nanocellulose composite and experiment on repairing hair scales (1) Collect adult female hair, wash it, and soak it in 5% ammonia water. Incubate it at 50°C for 2 hours, take it out and wash it to prepare simulated damaged hair with split hair scales.

[0126] (2) Take 1% of TJ-300 (Zeta potential -49 mV at pH 7.0), TJ-321T (Zeta potential -47 mV at pH 7.0), and QCNF (Zeta potential +15 mV / +46 mV / +79 mV at pH 7.0) nanocellulose prepared in Preparation Examples 1-3, respectively, and mix them with 1% keratin (Zeta potential -26 mV at pH 7.0) aqueous solution (modified nanocellulose and keratin are mixed in equal volumes), and treat them by high-speed vortex oscillation (2000-3000 rpm) for 5-10 minutes to obtain a solution containing keratin-nanocellulose complex, and immerse damaged hair with split hair scales therein (immerse 10 hairs of 10 cm in 10 mL of the mixed solution), incubate at 37°C for 8 hours, take out and wash, and obtain repaired hair.

[0127] (3) After drying, a scanning electron microscope was used to observe the results. Figure 3 shown.

[0128] The above is a description of the exemplary embodiments of the present invention. However, the protection scope of the present application is not limited to the above embodiments. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A composition, characterized in that The composition comprises cellulose and an active substance, wherein the Zeta potential or charging property of the active substance is opposite to that of the cellulose, wherein the absolute value of the Zeta potential of the active substance is 10-100 mV, and the sum of the absolute values ​​of the Zeta potentials of the cellulose and the active substance is 25-200 mV.

2. The composition according to claim 1, characterized in that The cellulose forms a complex or composite with the active substance.

3. The composition according to claim 1, characterized in that The absolute value of the cellulose Zeta potential is 15-100 mV; Alternatively, the active substance is selected from biologically active proteins or biologically active peptides.

4. The composition according to claim 3, characterized in that The absolute value of the cellulose Zeta potential is 30-50 mV; Alternatively, the absolute value of the Zeta potential of the active substance is 30-40 mV.

5. The composition according to claim 1, characterized in that The sum of the absolute values ​​of the Zeta potential of the cellulose and the active substance is 60-90 mV.

6. The composition according to claim 1, characterized in that The cellulose is nanocellulose, the diameter of which is less than 100 nanometers, or the aspect ratio of which is greater than 50.

7. The composition according to claim 6, characterized in that The cellulose is nanocellulose, and its diameter is 5-20 nanometers; or its aspect ratio is greater than 200.

8. The composition according to claim 1, characterized in that The cellulose is modified cellulose obtained by converting hydroxyl groups in cellulose into groups having positive or negative charges.

9. The composition according to claim 8, characterized in that The modified cellulose is a modified cellulose having a negative charge obtained by substituting a hydroxyl group in the cellulose with a carboxymethyl group, a carboxyl group, a phosphoric acid group or a sulfonic acid group; or a modified cellulose having a positive charge obtained by substituting a hydroxyl group in the cellulose with a quaternary ammonium group.

10. The composition according to claim 1, characterized in that The active substance is selected from keratin, silk protein, collagen, cell growth factor, polypeptide, oligopeptide or cyclic peptide.

11. The composition according to claim 1, characterized in that The Zeta potential of the cellulose and active substances in the composition is controlled by adjusting the pH value of the system, and the pH is adjusted within the range of 3-11.

12. The composition according to claim 1, characterized in that The composition also includes a cellulase enzyme.

13. The composition according to claim 12, characterized in that The cellulase comprises at least one of endo-enzyme, exo-enzyme and glucosidase.

14. The composition according to claim 12, characterized in that The cellulase has one or both of the following conditions: (1) The added amount of the cellulase is 100-500 U / g, based on the absolute dry weight of cellulose; (2) The filter paper enzyme activity of the cellulase is 30-60 U / mg.

15. The composition according to claim 1, characterized in that The surface adsorption rate of the cellulose in the composition to the active substance is: an adsorption rate of 60% or more after 5 hours of adsorption; or an adsorption rate of 85% or more after 10 hours of adsorption.

16. A method for preparing the composition according to claim 1, the method comprising: (S1) preparing a solution of the active substance; (S2) adding the cellulose solution to (S1) and mixing; And also including optional steps (S3) and (S4): (S3) preparing a cellulase solution and refrigerating it for later use; (S4) Mixing the cellulase solution in step (S3) and the solution of the composition obtained in step (S2).

17. The method according to claim 16, characterized in that The cellulose is modified cellulose, and the preparation method of the modified cellulose comprises: (SS1) The hydroxyl groups on the cellulose surface are converted into groups with positive or negative charges; And also includes the optional step (SS2): (SS2) After step (SS1), high pressure homogenization is performed.

18. The method according to claim 16 or 17, characterized in that The concentration of the active substance solution in step (S1) is 0.01-25wt%; Alternatively, the step (S1) further comprises adjusting the pH of the solution of the active substance after preparing the solution, wherein the pH is adjusted to a range between 3 and 11; Alternatively, the step (S2) further comprises adjusting the pH of the cellulose solution before mixing, wherein the pH is adjusted to a range between 3 and 11; Alternatively, step (S2) further comprises adjusting the pH of the formed complex or compound system after mixing, wherein the pH is adjusted to be within the range of 5-11; Alternatively, the rotation speed of the high-speed vortex oscillation in step (S4) is 2000-3000 rpm, and the oscillation time is 5-10 minutes.

19. Use of the composition according to any one of claims 1 to 15 in the preparation of medicines for repairing damaged skin, healing wounds, and treating skin diseases.

20. A medicine for repairing damaged skin, healing wounds, and treating skin diseases, characterized in that: The medicine comprises the composition according to any one of claims 1 to 15.

21. Use of the composition according to any one of claims 1 to 15 in daily chemical products.

Citation Information

Patent Citations

  • Composite scaffold material and preparation method and application thereof

    CN110064074A

  • Antibacterial peptide modified nanocellulose hydrogel, preparation method and application thereof

    CN114569488A

  • Antibacterial wound dressing and preparation method thereof

    CN117159781A

  • Preparation method of gradient fiber membrane and gradient fiber membrane

    CN117626654A

  • Collagen-based composite hydrogel as well as preparation method and application thereof

    CN117736466A